A qualitative study of the costs experienced by caregivers of children being treated for cancer in New Delhi, India. Issue 3 (8th November 2018) - Mardakis, Stephanie; Arora, Ramandeep S.; Bakhshi, Sameer; Arora, Ashima; Anis, Huma; Tsimicalis, Argerie
Abstract: Background: The allocation of time and other resources is essential to enable the treatment of children with cancer. Evidence derived from high‐income countries showcases the significant costs families may incur impacting their finances and lifestyle. However, there is a paucity of research examining the costs of childhood cancer in India, which may impact families' decision to abandon their child's treatment. Aim: The aim of this study was to explore the costs experiences by caregivers of children undergoing pediatric cancer treatment in New Delhi, India. Methods: A qualitative descriptive study was conducted in three cancer institutions in New Delhi. Semistructured interviews were conducted with caregivers of children with cancer in English or Hindi. Interviews were transcribed verbatim, translated into English, and analyzed using a thematic approach. Results: In total, 25 caregivers of 24 children diagnosed with cancer participated in the study. Caregivers described direct, indirect, and psychosocial costs associated with their child's treatment. The primary sources of direct costs were hospital admissions, medications, food, and travel expenses. Indirect costs involved managing their child's treatment, affecting caregivers' sleep, work hours, and time spent with other family members. Psychosocial costs included coping with the uncertainty caused by a cancer diagnosis, feelings of guilt, and sadness as well as having to watch their children suffer. Caregivers accessed a network of support to cope with their child's treatment. No families abandoned treatment or indicated that they intended to do so. Conclusions: The results of this study provide avenues for health care professionals and institutions to develop interventions aimed at reducing the costs associated with cancer treatment. Further research into the relationship between various costs and treatment abandonment is needed.